Two outbreaks of mixed etiology associated with central venous catheters inserted by phlebotomy in critical neonates - Brito,Denise V.D. de (2009)
Staphylococcus aureus and coagulase-negative staphylococci are the main cause of sepsis in Neonatal Intensive Care Unit (NICU). Central venous catheters (CVCs) are an important part of critical neonates' treatment and are associated with sepsis. The aim of this study was to investigate two outbreaks caused by Staphylococcus aureus and Staphylococcus epidermidis associated with CVC inserted by phlebotomy in critical neonates. The surveillance was performed from January 2001 to December 2005 at the Brazilian NICU. The genotypic analysis of oxacillin susceptible S. aureus (OSSA) and oxacillin resistant S. epidermidis (ORSE) was performed based on pulsed-field gel electrophoresis (PFGE). Staphylococcus was the most frequent pathogen (65.8%) with highest incidence of CoNS (59.9%) followed by S. aureus (40.1%). During the five years of surveillance, there were two outbreaks detected, occurred in January-February/02 and August/02 and confirmed by PFGE analysis. The predisposing factors for infection corresponding to both outbreaks were: age <7 days, hospitalization > 7 days, and use of polyethylene CVC through dissection of vein (phlebotomy). This is the first relate of staphylococcal outbreaks associated with CVC inserted by phlebotomy in NICU. PFGE showed polyclonal spread of OSSA during both epidemic and endemic period, and two monoclonal outbreaks of ORSE in the same epidemic period of OSSA.